2018
DOI: 10.28991/cej-03091165
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Infrastructure Resilience in Disasters Using Dynamic Network Analysis of Consumers’ Service Disruption Patterns

Abstract: This study proposes a network analysis framework for characterizing infrastructure resilience in the aftermath of disasters through the use of consumers’ service disruption information. In the presented framework, the notion of “peers” is used to construct the network models of consumers experiencing service disruption in the aftermath of a disaster to understand the type and extent of infrastructure damages and specify disruption patterns. Data related to electricity disruption in Bhaktapur, Nepal, in the aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 37 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…This is to mean that, by considering other survey results, both cities are practicing the principles without understanding the concept of urban resilience (Figure 5). This finding is consistent with the findings of [29] who reported on incorporating all stakeholders in decision-making improves legitimacy, expanding the depth and diversity of knowledge, and helping to detect and interpret change and disruptions. They further argued that resilience grows as the network of stakeholders strengthens linkages in the system (Figure 6).…”
Section: Urban Resilience Principlessupporting
confidence: 90%
See 1 more Smart Citation
“…This is to mean that, by considering other survey results, both cities are practicing the principles without understanding the concept of urban resilience (Figure 5). This finding is consistent with the findings of [29] who reported on incorporating all stakeholders in decision-making improves legitimacy, expanding the depth and diversity of knowledge, and helping to detect and interpret change and disruptions. They further argued that resilience grows as the network of stakeholders strengthens linkages in the system (Figure 6).…”
Section: Urban Resilience Principlessupporting
confidence: 90%
“…Studies indicated that everyday life relies on the operation of different Resilience of Civil Infrastructure Systems (CISs), such as electric power, water and gas distribution, and transportation infrastructures [29]. However, consideration of incorporating the concept of urban resilience into the urban planning and design fields to prevent the natural disasters has limited practice in developing countries and in Ethiopia too.…”
Section: Urban Infrastructure Resiliency To Disasters and Urban Resil...mentioning
confidence: 99%
“…e mobility of UAVs causes the distance between any two nodes in FANETs to vary with time, and the conventional interference model can only obtain the cumulative interference value at time t (called the instantaneous interference value) [17], which does not accurately reflect the current channel state. Also, the fast mobility makes it very difficult for the UAV to obtain the state information of all channels, and the instantaneous interference value can only reflect the current channel state, so it is necessary to find a method that can satisfy the variation of the distance between nodes and accurately reflect the current channel state.…”
Section: Equalization Analysis Of Medical Facility Networkmentioning
confidence: 99%
“…For these reasons, active FTC system received great attention among the researchers [43,[56][57][58][59][60][61][62][63][64][65].…”
Section: Passive Ftcmentioning
confidence: 99%